Facebook Online Shop Alternatif Bisnis & Belanja dalam Jejaring Sosial - , RETNO ARI WIJAYANTI; , Dr. Anna Marie Wattie ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Facebook emerged as one of fast growing, and quickly spread communication tools within the society all around the world. The highly significant participation rate in Indonesia gives Facebook the opportunity to be the mainstay of social networking site within the country. Indonesian society become more aware of this opportunity, then creatively use Facebook as a platform to perform trading activities. The activity of buying and selling within Facebook relates the online shop phenomenon or also specifically known as the F-shop. This study tries to explain how the F-shop phenomenon is present within the Indonesian community through three questions. First,why do the online shop entrepreneurs choose to use Facebook for business